2020
DOI: 10.1002/cbdv.201900489
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Antioxidant Activity of Essential Oil of Chinese Propolis

Abstract: The chemical composition and in vitro antioxidant activity of the essential oil of propolis (EOP) collected from 25 locations in China was investigated. Steam-distillation extraction was used to extract the EOP, and chemical composition was identified by GC/MS. The antioxidant activities of EOP were also measured. The result showed that a total of 406 compounds were detected in EOP. The major compounds of Chinese EOP were cedrol, γ-eudesmol, benzyl alcohol, phenethyl alcohol, 2-methoxy-4-vinylphenol, 3,4-dimet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 26 publications
0
27
0
Order By: Relevance
“…Essential/volatile oils are major bioactive constituents of propolis, and they contribute to its special aroma [ 79 , 80 ]. They also, partially, contribute to the strong antimicrobial, antioxidant, and anticancer activities of propolis [ 79 , 81 , 82 ]. The volatile fraction of propolis varies in each sample even within a single country due to plant source and climate [ 79 ].…”
Section: Apitherapy As a Possible Complementary Treatment For Sarcmentioning
confidence: 99%
See 2 more Smart Citations
“…Essential/volatile oils are major bioactive constituents of propolis, and they contribute to its special aroma [ 79 , 80 ]. They also, partially, contribute to the strong antimicrobial, antioxidant, and anticancer activities of propolis [ 79 , 81 , 82 ]. The volatile fraction of propolis varies in each sample even within a single country due to plant source and climate [ 79 ].…”
Section: Apitherapy As a Possible Complementary Treatment For Sarcmentioning
confidence: 99%
“…They also, partially, contribute to the strong antimicrobial, antioxidant, and anticancer activities of propolis [ 79 , 81 , 82 ]. The volatile fraction of propolis varies in each sample even within a single country due to plant source and climate [ 79 ]. For instance, cumulative knowledge shows that volatile oils in propolis found in countries surrounding the Mediterranean depend mainly on the botanical origin.…”
Section: Apitherapy As a Possible Complementary Treatment For Sarcmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, 87 compounds were identified, demonstrating the diverse chemical composition of the volatile compounds in the propolis. Chi et al [ 25 ] identified approximately 406 compounds, mainly comprising monoterpenes, phenol alcohols, sesquiterpenoids, acid esters, aldoketones, and hydrocarbons. However, in the present study, the predominant classes were sesquiterpene hydrocarbons (80.6–89.2%), followed by oxygenated monoterpenes (3.6–8.4%).…”
Section: Resultsmentioning
confidence: 99%
“…Cedrol is a natural crystalline sesquiterpene alcohol found in the essential oil of conifers especially cedar wood ( Juniperus virginiana ). The antioxidant activity of the essential oil of propolis containing cedrol was detected recently ( Chi et al, 2020 ). The pharmacokinetics and pharmacodynamics of cedrol polymorphs were associated with anti-inflammatory and analgesic effects in a mouse paw edema model induced by xylene ( Wang et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%